The New Consultant's Quick Start Guide : an Action Plan for Your First Year in Business. - Biech, Elaine (John Wiley & Sons, Incorporated, 2019)
An action plan for working as a consultant Management consulting is a $250 billion industry and growing at a rate of over four percent annually. Many predict that more than 40 percent of the U.S. workforce will soon be contingent, freelance, or consulting members of the workforce--making this book more relevant than ever. Individuals become independent consultants out of necessity or preference: necessity because they lost their job or the company offered an attractive exit package; preference because they want a career change, more control over their time, or an enriched, varied work situation. Consulting also appeals to the Millennial workforce who are searching for careers that offer a good salary as well as meaningful work. The New Consultant's Quick Start Guide: • Serves as a companion to The New Business of Consulting • Provides you with a place to plan your transition into consulting • Helps you identify your niche, develop a business plan, charge what you're worth, and create a marketing strategy to ensure a steady stream of clients • Prepares you for changes you will encounter beyond your professional life, including social, family, and financial aspects The New Consultant's Quick Start Guide helps you work through the challenges of consulting such as working alone, deciding on necessary insurance coverage, finding your first clients, struggling with cash flow, and understanding market trends.